Symplectic Schemes for Linear Stochastic Schrödinger Equations with Variable Coefficients - Xiuling Yin; Yanqin Liu (Abstract and Applied Analysis)
This paper proposes a kind of symplectic schemes for linear Schrödinger equations with variable coefficients and a stochastic perturbation term by using compact schemes in space. The numerical stability property of the schemes is analyzed. The schemes preserve a discrete charge conservation law. They also follow a discrete energy transforming formula. The numerical experiments verify our analysis.